2014
DOI: 10.1515/ii-2017-0071
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Clinical Characteristics of 28 Cases of Cholera

Abstract: The data of 35 246 patients with intestinal diseases were retrospectively analyzed, 28 cases of cholera patients were screened in 17 years, of which 23 cases had suspicious unclean food history, 10 cases were migrant workers, 8 cases had history of coastal city tour in one week. All of the 28 patients were positive for Vibrio cholerae culture, 19 cases were identified as O1 serotype Ogawa and 6 were identified as O1 serotype Inaba, 3 were identified as O139. Twenty-three patients were mild, five cases were mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Five of these articles covered 491 cases in the USA between 1965 and 2011, of which 342 were acquired outside the USA 22 , 23 , 25 , 26 , 28 . One article covered 129 cases imported into France from 1973 to 2005 24 and a seventh review article reported 28 cases occurring in China from 1995 to 2012, most of which were associated with eating unclean food rather than due to travel 27 …”
Section: Resultsmentioning
confidence: 99%
“…Five of these articles covered 491 cases in the USA between 1965 and 2011, of which 342 were acquired outside the USA 22 , 23 , 25 , 26 , 28 . One article covered 129 cases imported into France from 1973 to 2005 24 and a seventh review article reported 28 cases occurring in China from 1995 to 2012, most of which were associated with eating unclean food rather than due to travel 27 …”
Section: Resultsmentioning
confidence: 99%